Desain Microstrip Antenna, Open Dipole, dan Folded Dipole 1090 MHZ pada Peralatan Penerima Automatic Dependent Surveillance-Broadcasting - Ade Handayani (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2022)
ADS-B (Automatic Dependent Surveillance-Broadcasting) system is a system for detecting the position of an aircraft. The system uses pi aware software which is used as software that displays a virtual map of the location of the aircraft. The purpose of this study was to find results in the form of parameters of the Farthest or best ADS-B reception distance by comparing three types of antennas, namely Microstrip antennas, open dipole antennas, and Folded Dipole antennas at a frequency of 1090 MHz using pi aware applications. The problem found in the current radar system is the detection that is affected by weather conditions so the level of stabilization in the reception sensitivity of each antenna is very dependent on natural conditions. Data collection is carried out by placing the position of the antenna or receiver in the field, which is an open place. The results of the study were obtained with the farthest distance of 132.7884 km, which is found in the Open dipole area. From the series of tests and data collection carried out, it can be seen that the tools are designed in accordance with the planning and research objectives